Farmers' Perception and Engagement with the Role of Middlemen: A Case Study of the Vegetable Farmers - Sudrajat, Jajat; Isytar, Ibrahim; Arifin, Nur (Makara Human Behavior Studies in Asia, 2021)
The role of middlemen in rural areas is often controversial, particularly because of the positive or negative roles they play in the farmer livelihood. This study aims to understand the farmers' perception of the role of middlemen in facilitating their farming system and to find out the socioeconomic factors that determine to what degree farmers attach themselves to middlemen. To get this information, we conducted a case study survey of 92 respondents from the subdistrict of Rasau Jaya, Kubu Raya, West Kalimantan, Indonesia. Approximately 95% of the farmers had a positive perception of the role of the middlemen, which was considered important in the farm produce marketing and also the transportation of both fertilizer and crops. Older farmers, farmers with a higher education level, and farmers with more vegetable commodities were less attached to the middleman in the marketing of their agricultural products. These farmers often changed the middleman to get a higher price. Conversely, farmers producing sweet maize and farmers with a higher income level were more attached to a middleman. A high level of engagement with a middleman is one of the farmer strategies to avoid marketing risks.